IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 2 PARE KEDIRI - Rohmawan, Dhuhaa; Fattah, Rifky (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2024)
This research aims to find out how the process of implementing the Kurikulum Merdeka in the subjects of Islamic Education and Character, what the obstacles to implementation are, and how schools try to overcome these obstacles. In this research, researchers used qualitative research methods with a descriptive approach. Data collection techniques use observation, interviews and documentation. Data analysis techniques use the Miles & Huberman model, namely data reduction, data presentation, drawing conclusions/verification. The results of this research show that the implementation of the Kurikulum Merdeka in the subjects of Islamic Education and Character is going well, the indicators are teacher preparation carried out by teachers, preparation of learning tools, implementation of the learning process, and implementation of the Projek Penguatan Profil Pelajar Pancasila (P5). The problems found in this research are that teachers have not received training, differentiated learning is not optimal, as well as changes in the paradigm of teachers and students. And efforts to overcome the problems of implementing the Kurikulum Merdeka in the subjects of Islamic Education and Character at SMA Negeri 2 Pare are by attending workshops, increasing a teacher's creativity and sharing to change the mindset in teaching.